Diversity patterns of uncultured Haptophytes unravelled by pyrosequencing in Naples Bay - Lucie Bittner; Angélique Gobet; Stéphane Audic; Sarah Romac; Elianne S. Egge; Sébastien Santini; Hiroyuki Ogata; Ian Probert; Bente Edvardsen; Colomban de Vargas (Molecular Ecology, 2013)
Haptophytes are a key phylum of marine protists, including ~300 described morphospecies and 80 morphogenera. We used 454 pyrosequencing on large subunit ribosomal DNA (LSU rDNA ) fragments to assess the diversity from size‐fractioned plankton samples collected in the Bay of Naples. One group‐specific primer set targeting the LSU rDNA D1/D2 region was designed to amplify Haptophyte sequences from nucleic acid extracts (total DNA or RNA) of two size fractions (0.8–3 or 3–20 μm) and two sampling depths [subsurface, at 1 m, or deep chlorophyll maximum (DCM) at 23 m]. 454 reads were identified using a database covering the entire Haptophyta diversity currently sequenced. Our data set revealed several hundreds of Haptophyte clusters. However, most of these clusters could not be linked to taxonomically known sequences: considering OTUs 97% (clusters build at a sequence identity level of 97%) on our global data set, less than 1% of the reads clustered with sequences from cultures, and less than 12% clustered with reference sequences obtained previously from cloning and Sanger sequencing of environmental samples. Thus, we highlighted a large uncharacterized environmental genetic diversity, which clearly shows that currently cultivated species poorly reflect the actual diversity present in the natural environment. Haptophyte community appeared to be significantly structured according to the depth. The highest diversity and evenness were obtained in samples from the DCM, and samples from the large size fraction (3–20 μm) taken at the DCM shared a lower proportion of common OTUs 97% with the other samples. Reads from the species Chrysoculter romboideus were notably found at the DCM, while they could be detected at the subsurface. The highest proportion of totally unknown OTUs 97% was collected at the DCM in the smallest size fraction (0.8–3 μm). Overall, this study emphasized several technical and theoretical barriers inherent to the exploration of the large and largely unknown diversity of unicellular eukaryotes.